Transnational Education- Leadership in transnational education and internationalisation of curriculum - Mazzolini, Margaret; Yeo, Shelley; Ling, Peter; Goerke, Veronica; Giridharan, Beena; Lueckenhausen, Gillian (Office of Learning and Teaching, 2012)
Learning Without Borders was funded as an ALTC Leadership project. The project was conducted by Swinburne University of Technology and Curtin University in Australia and on their Sarawak campuses in Malaysia. The project focuses on leadership roles in the conduct of transnational education (TNE) and in the internationalisation of curriculum. For purposes of the project, TNE is defined as an arrangement for provision of higher education where students acquire an award in one country issued by a higher education institution based in another country.The project focused on developing recognition, reward and support of leaders in TNE and in internationalisation of curriculum. The project involved an investigation of staff experiences, expectations and preferences in TNE and in the internationalisation of curriculum. It included matters such as influences of involvement in TNE on career paths and on learning and teaching, views on good practice in TNE and internationalisation of curriculum. Through the project online professional development modules aimed at supporting leaders and academics engaged in TNE were produced. The modules have been designed so that they may be customised by other Australian universities. The project produced recommendations on recognition, reward and support of leadership in TNE and internationalisation of curriculum and guides in the form of a handbook and checklists.